Rebalancing the economy and reforming the fiscal system of the People Republic of China. - Bahl, Roy; Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
Certain possible reforms in the intergovernmental fiscal structure are consistent with the objectives of high-quality economic growth and the improvement of human well-being in the PRC. Some of these changes would involve more fiscal decentralization and some would lead to more fiscal centralization. Most are in the mode of offering subnational government leaders more autonomy in choosing their fiscal strategy but with incentives to make choices that are consistent with central government objectives. An alternative approach to sweeping institutional change would be to maintain the present intergovernmental fiscal structure and meet the desired objectives with mandates on service levels, as well as direct interventions in the expenditure regime such as conditional transfers or changes in budgeting practices.
Keywords: Fiscal policy -- China; Finance, Public -- China; Economic stabilization -- Government policy -- China; Electronic book